PPARα Agonist WY-14643 Relieves Neuropathic Pain through SIRT1-Mediated Deacetylation of NF-κB - Wanshun Wen; Jinlin Wang; Biyu Zhang; Jun Wang (PPAR Research)
Inflammation caused by neuropathy contributes to the development of neuropathic pain (NP), but the exact mechanism still needs to be understood. Peroxisome proliferator-activated receptor α (PPARα), an important inflammation regulator, might participate in the inflammation in NP. To explore the role of PPARα in NP, the effects of PPARα agonist WY-14643 on chronic constriction injury (CCI) rats were evaluated. The results showed that WY-14643 stimulation could decrease inflammation and relieve neuropathic pain, which was relative with the activation of PPARα. In addition, we also found that the SIRT1/NF-κB pathway was involved in the WY-14643-induced anti-inflammation in NP, and activation of PPARα increased SIRT1 expression, thus reducing the proinflammatory function of NF-κB. These data suggested that WY-14643 might serve as an inflammation mediator, which may be a potential therapy option for NP.